Serat Centhini - Chodjim, Achmad (Baca, 2019)
On Centhini, a Javanese classic poem on Javanese journey of life Criticism and interpretation of Centhini, a Javanese classical poem
Keywords: Hochschulschrift; Epic poetry; Javanese; Javanese literature